2014
DOI: 10.1016/j.ttbdis.2013.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Ticks and spotted fever group rickettsiae of southeastern Virginia

Abstract: The incidence of tick-borne rickettsial disease in the southeastern United States has been rising steadily through the past decade, and the range expansions of tick species and tick-borne infectious agents, new and old, has resulted in an unprecedented mix of vectors and pathogens. The results of an ongoing 4-year surveillance project describe the relative abundance of questing tick populations in southeastern Virginia. Since 2009, more than 66,000 questing ticks of 7 species have been collected from vegetatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
66
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 31 publications
2
66
0
Order By: Relevance
“…The results of this study are consistent with the findings of others in that only R. montanensis was detected at a low prevalence in D. variabilis ticks. Previous studies in Canada and the United States have indicated a mean prevalence of 1.5% to 9.8% of R. montanensis in D. variabilis (Dergousoff et al, 2009;Teng et al, 2011;Yunik et al, 2015;Ammerman et al, 2004;Carmichael and Fuerst, 2010;Moncayo et al, 2010;Nadolny et al, 2014;Pagac et al, 2014;Smith et al, 2010;Stromdahl et al, 2011). The pathogenicity of R. montanensis is currently unclear.…”
Section: Discussionmentioning
confidence: 96%
“…The results of this study are consistent with the findings of others in that only R. montanensis was detected at a low prevalence in D. variabilis ticks. Previous studies in Canada and the United States have indicated a mean prevalence of 1.5% to 9.8% of R. montanensis in D. variabilis (Dergousoff et al, 2009;Teng et al, 2011;Yunik et al, 2015;Ammerman et al, 2004;Carmichael and Fuerst, 2010;Moncayo et al, 2010;Nadolny et al, 2014;Pagac et al, 2014;Smith et al, 2010;Stromdahl et al, 2011). The pathogenicity of R. montanensis is currently unclear.…”
Section: Discussionmentioning
confidence: 96%
“…5,10 Similarly, tick surveys conducted in neighboring states in the southeastern region revealed the same pattern of the predominance of R. amblyommii in Amblyomma americanum ticks, the most ubiquitous and aggressive tick species in this region. 8,15,22,23 Finally, an Oklahoma study in canines used as sentinels for rickettsial diseases, also showed similar results. Dogs were naturally infected with R. amblyommii and R. montanensis after tick exposure.…”
Section: Discussionmentioning
confidence: 54%
“…Numerous tick surveys, including those conducted in Tennessee, have shown the absence of R. rickettsii but the presence of other SFG Rickettsia such as Rickettsia amblyommii, Rickettsia Parkeri, and Rickettsia montanensis. [5][6][7][8][9][10] The contradicting reports of increasing incidence of SFG rickettsiosis (including RMSF) and the rarity of R. rickettsii in ticks raise the likelihood that other SFG rickettsiae species are contributing to this increase in incidence. Previous studies have demonstrated evidence for infection with other less pathogenic SFG rickettsiae species that clinically resemble RMSF.…”
Section: Introductionmentioning
confidence: 99%
“…'Candidatus R. amblyommii' has since been identified as a common Rickettsia in ticks of North and South America, especially those of the genus Amblyomma (Mixson et al, 2006;Labruna et al, 2011). In some areas, its prevalence in ticks can be higher than 50% (Bermúdez et al, 2009;Jiang et al, 2010;Zhang et al, 2012;Blanton et al, 2014;Nadolny et al, 2014).…”
Section: Introductionmentioning
confidence: 99%